Palaeoglaciology of Bayan Har Shan, NE Tibetan Plateau: exposure ages reveal a missing LGM expansion - Heyman, Jakob; Stroeven, Arjen P.; Caffee, Marc W.; Hattestrand, Clas; Harbor, Jonathan M.; Li, Yingkui; Alexanderson, Helena; Zhou, Liping; Hubbard, Alun (Quaternary Science Reviews, 2011)
The Bayan Har Shan, a prominent upland area in the northeastern sector of the Tibetan Plateau, hosts an extensive glacial geological record. To reconstruct its palaeoglaciology we have determined Be-10 exposure ages based on 67 samples from boulders, surface pebbles, and sediment sections in conjunction with studies of the glacial geology (remote sensing and field studies) and numerical glacier modelling. Exposure ages from moraines and glacial sediments in Bayan Har Shan range from 3 ka to 129 ka, with a large disparity in exposure ages for individual sites and within the recognised four morphostratigraphical groups. The exposure age disparity cannot be explained by differences in inheritance without using unrealistic assumptions but it can be explained by differences in post-depositional shielding which produces exposure ages younger than the deglaciation age. We present a palaeoglaciological time-slice reconstruction in which the most restricted glaciation, with glaciers less than 10 km long, occurred before 40-65 ka. More extensive glaciations occurred before 60-100 ka and 95-165 ka. Maximum glaciation is poorly constrained but probably even older. The Bayan Hat Shan exposure age dataset indicates that glaciers on the northeastern Tibetan Plateau have remained surprisingly restricted for at least 40 ka, including the global last glacial maximum (LGM). This case of a missing LGM is further supported by high-resolution glacier modelling experiments. (C) 2011 Elsevier Ltd. All rights reserved. Geography, Physical Geosciences, Multidisciplinary SCI(E) EI 21 ARTICLE 15-16 1988-2001 30